Тема єгипетської Книги Мертвих у дослідженнях українського сходознавця Миколи Тарасенка - Білик, Вікторія Андріївна; Bilyk, Viktoria (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті виконано аналіз новітніх українських досліджень з історії Стародавнього Єгипту. Зокрема, увагу зосереджено на науковому доробку фахівця в галузі єгиптології, археології, мистецтвознавства та релігієзнавства, доктора історичних наук, старшого наукового співробітника відділу Близького і Середнього Сходу Інституту cходознавства ім. А. Ю. Кримського НАН України Миколи Тарасенка. Він займається дослідженням та вивченням єгипетської Книги Мертвих – одного з найоригінальніших писемних джерел з історії Стародавнього Єгипту.Based on the analysis of the scientific heritage of one of the modern Ukrainian historian Mykola Tarasenko, expert in the field of Egyptology, archaeology, art history and religious studies, doctor of historical Sciences, senior researcher of the Department of the Middle East Institute of Oriental studies named after A. Y. Krymskiy Ukrainian National Academy of Science, we made an attempt to identify priority areas of the egyptologiques studies in the modern Ukrainian historical science. Such is certainly true of religious themes as a feature of not only ancient Egypt but also other countries of the Ancient East, is the deep penetration of religion into all spheres of life, the influence of the religious factor in ancient times was decisive. It is therefore quite natural that the interest of researchers sources on the history of ancient Egypt have a religious basis. Such is the Book of the dead. It became the subject of scientific investigation of Nikolay Tarasenko.
The Theme of the Egyptian Book of the Dead in the Research of the Ukrainian Orientalist Nikolay Tarasenko
Keywords: історіографія; єгиптологія; дослідження; джерело; Стародавній Єгипет; Книга Мертвих; historiography; egiptologia; research; source; Ancient Egypt; Book of the dead